2011
DOI: 10.1016/j.jcrs.2011.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Scheimpflug densitometry as a measure of corneal optical density after excimer laser refractive surgery in myopic eyes

Abstract: An early increase and a subsequent reduction in anterior corneal optical density and the refractive index were present in myopic eyes during 1 year after PRK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…14 Previous studies reported corneal densitometry values of 16.76 ± 1.87 GSU, which is similar to our preoperative values: 16.62 ± 1.97 for LASIK, 16.38 ± 1.67 for PRK, and 16.26 ± 1.50 for ReLEx SMILE. 15,16,30 Previous studies have also evaluated corneal densitometry in PRK and LASIK patients both before and after surgery. [14][15][16] As for post-PRK patients, the 3-month postoperative value was 37.81 GSU, and the 12 month one was 26.92 GSU, 15 which is twice the value found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Previous studies reported corneal densitometry values of 16.76 ± 1.87 GSU, which is similar to our preoperative values: 16.62 ± 1.97 for LASIK, 16.38 ± 1.67 for PRK, and 16.26 ± 1.50 for ReLEx SMILE. 15,16,30 Previous studies have also evaluated corneal densitometry in PRK and LASIK patients both before and after surgery. [14][15][16] As for post-PRK patients, the 3-month postoperative value was 37.81 GSU, and the 12 month one was 26.92 GSU, 15 which is twice the value found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,30 Previous studies have also evaluated corneal densitometry in PRK and LASIK patients both before and after surgery. [14][15][16] As for post-PRK patients, the 3-month postoperative value was 37.81 GSU, and the 12 month one was 26.92 GSU, 15 which is twice the value found in our study. Fares et al 16 found no significant differences between pre-and postoperative values for overall corneal densitometry following LASIK, and reported corneal densitometry values 12 months after surgery that were slightly lower than our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,32 Corneal densitometry has been assessed, and the degree of subepithelial corneal haze and stromal scarring in refractive surgery patients has been quantified. 9,10,12 Most studies used slitlamp observation and subjective assessment to report haze after keratorefractive surgery. However, objective assessments are more accurate and more repeatable than subjective ones.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recently, subepithelial haze and stromal scarring after laser surgery have been quantified and assessed objectively using a Scheimpflug-imaging technique incorporated into different commercial units. [8][9][10] The Pentacam (Oculus Optikger€ ate GmbH) is a noninvasive optical system that uses the Scheimpflug principle to take up to 50 cross-sectional images of the entire anterior segment within 2 seconds. 11 The ability to measure changes in corneal transparency noninvasively and objectively may enable more precise monitoring of progression and may improve patient management.…”
mentioning
confidence: 99%